Analysis of the Influence of Institutional Image, Zakat Institution Performance and Trust on Muzakki Satisfaction (Study on Baznas Semarang City) - Aulya Rahmawati; Zainal Alim Adiwijaya (LP2M IAIN Palopo, 2026)
This study addresses the main problem of challenges in maintaining the trust and satisfaction of muzakki amidst the demands of professional zakat management. This study aims to examine the influence of institutional image, zakat institution performance, and trust on muzakki satisfaction at BAZNAS Semarang City. This study uses a quantitative method with a purposive sampling technique on 130 respondents from a population of 2,996 muzakki as of July 2025, the data were analyzed using SEM-PLS through SmartPLS software version 4.1.1.4. The results show that institutional image, zakat institution performance, and trust have a positive and significant effect on muzakki satisfaction. This model has a value of of 0.747 (Adjusted = 0.741) which shows that the three independent variables are able to explain 74.1% of the variation in muzakki satisfaction in the strong category. This data is supported by a summary of open-ended responses, which indicate that the friendliness of officers, ease of processing through digital services, and transparency of zakat distribution are the aspects most appreciated by respondents. This study was limited to the scope of BAZNAS Semarang City with three independent variables. Future research is recommended to develop variables such as reporting transparency, service innovation, and the tangible impact of zakat empowerment programs. This study provides insight into muzakki satisfaction at the regional level by enriching the interpretation of the results through respondents' aspirations regarding digital services and distribution transparency.